{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

Section 3.6-problems-1

# Section 3.6-problems-1 - troyer(lmt836 Section 3.6...

This preview shows pages 1–2. Sign up to view the full content.

troyer (lmt836) – Section 3.6 – isaacson – (55826) 1 This print-out should have 6 questions. Multiple-choice questions may continue on the next column or page – find all choices before answering. 001 10.0points Find y when xy + 3 x + 4 x 2 = 1 . 1. y = - y + 3 + 4 x x 2. y = - ( y + 3 + 8 x ) 3. y = y + 3 + 8 x x 4. y = 3 + 4 x - y x 5. y = y + 3 + 4 x x 6. y = - y + 3 + 8 x x 002 10.0points If y = y ( x ) is defined implicitly by y 2 + xy + 3 = 0 , find the value of dy/dx at the point (4 , - 1). 1. dy dx vextendsingle vextendsingle vextendsingle (4 , 1) = - 1 2 2. dy dx vextendsingle vextendsingle vextendsingle (4 , 1) = - 3 2 3. dy dx vextendsingle vextendsingle vextendsingle (4 , 1) = 1 2 4. dy dx vextendsingle vextendsingle vextendsingle (4 , 1) = 3 2 5. dy dx vextendsingle vextendsingle vextendsingle (4 , 1) = - 1 6. dy dx vextendsingle vextendsingle vextendsingle (4 , 1) = 1 003 10.0points Find dy dx when tan( xy ) = 2 x - y. 1. dy dx = 2 - y sec 2 ( xy ) x sec 2 ( xy ) - 1 2. dy dx = 1 - x sec 2 ( xy ) y sec 2 ( xy ) + 2 3. dy dx = 2 - y sec 2 ( xy ) x sec 2 ( xy ) + 1 4. dy dx = 1 - x sec 2 ( xy ) y sec 2 ( xy ) - 2 5. dy dx = 2 + y sec 2 ( xy ) x sec 2 ( xy ) + 1 6. dy dx =

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}